Publisher Correction: Livestock husbandry in Islamic Cártama, Málaga, Spain: The micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2026)

Livestock husbandry in Islamic Cártama, Málaga, Spain: the micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2025)
Multidisciplinary micro- and bioarchaeological analyses of late medieval deposits from suburban Cártama, Málaga, Spain, have, for the first time, confidently identified open air fumier deposits, which are supported by preliminary analysis of the faunal assemblage. This demonstrates that Andalusi livestock husbandry practices included periodically burning animal dung within corrals and pens, which is a long-standing practice in the Mediterranean region also observed in prehistoric transhumance. These techniques have commonly been applied to prehistoric fumier or pastoral sites and now demonstrate the importance of expanding micro- and bioarchaeological work to fumier sequences from other periods. This research from Cártama offers a window into the so-called medieval “Green Revolution” associated with Arab migrations and highlights the necessity of identifying in situ penning deposits on archaeological sites and of applying high resolution analyses to examine them. The analyses reveal data on animal feeds, including pearl millet ( Pennisetum glaucum ) and sorghum ( Sorghum bicolor ) which are rare in the Iberian Peninsula at this time, the use of plant resources in livestock husbandry, and the preparation of fertiliser, which are central to understanding farming practices in Al-Andalus.

Understanding late medieval farming practices: an interdisciplinary study on byre remains from the historical centre of Brussels (Belgium) - Yannick Devos; Cristiano Nicosia; Luc Vrydaghs; Jan M. A. van der Valk; Lien Speleers; Elena Marinova; Mona Court-Picon; Terry B. Ball; Christine Pümpin; Hugues Doutrelepont; Britt Claes (Archaeological and Anthropological Sciences, 2025)
During the preventive archaeological excavation in the cellar of the site of petite Rue des Bouchers in the historical centre of Brussels (Belgium), the waterlogged remains of a thirteenth century AD sunken byre (potstal) were discovered. The exceptional preservation instigated a multiproxy approach, including micro-archaeology, micromorphology, phytolith and endoparasite egg analysis on thin sections, palynology and the study of plant macroremains on the fill of the structure. Beyond permitting to detail the content and the multiple origins of the fill (including excremental waste and urines, fodder and bedding material, plaggen and/or soil sods, household and construction waste), this study also provides detailed insights into the foddering customs, hygienic conditions within the stable, and the health status of the animals kept. On a more general scale this study documented late medieval farming practices in Brussels, more specifically the need to collect substantial amounts of manure to add as fertilizer onto the cultivated poor sandy soils.

Colourful rivers: archaeobotanical remains of dye plants from urban fluvial deposits in the southern Low Countries (Belgium) - Lien Speleers; Ina Vanden Berghe; Valérie Ghesquière; Frank Kinnaer; Marc Meganck; Sidonie Preiss; Stephan Van Bellingen; Julie Timmermans; Yannick Devos (Vegetation History and Archaeobotany, 2025)

Anthropogenic soils and sediments from historical trade hub on the bank of Morava River in Uherské Hradiště (Czech Republic): Archives of mediaeval landscape, environment and settlement dynamics - Katarína Adameková; Jaroslav Bartík; Jan Petřík; Yannick Devos; Libor Petr; Petr Kočár; Romana Kočárová; Tomáš Chrástek; Marcin Frączek; Michal Kurka; Miloslav Pouzar (CATENA, 2025)

Auto-fluorescent phytoliths: can we detect past fires in tropical and subtropical contexts? - Marc Testé; Enrique Fernández-Palacios; Aline Garnier; Alvaro Castilla-Beltrán; Martin J. Hodson; Yannick Devos; Luc Vrydaghs (Vegetation History and Archaeobotany, 2025)